Spiritual Occlusion and Systemic Integrity: Legal Evaluations of Due Process Protections and Freedom of Religious Expression and Practices Safeguards - Jolicoeur, Jason R. (Religions, 2018)
As is the case with other constitutionally protected rights, the freedom of religion is not unlimited nor without restriction or constraint. Rather, the courts have long held that the state may have legitimate reasons for placing reasonable restrictions on the otherwise free exercise of religious practice. The courts have also held that the state cannot restrict religious practice in a capricious or gratuitous manner. However, the courts have also held that individuals have a constitutional right to due process legal protections. In many instances, these two freedoms exist independently of each other. In instances when they intersect, conflict may result from one right seeking hegemony over the other. In instances such as these, the courts may have to resolve conflicts by establishing legal principles and precedents regarding which of these constitutional protections will be granted contextual prominence over the other. Thus far, the legal evaluation of this important question has been confused at best and contradictory at worst. This has resulted in a number of substantive outcomes that pose significant challenges to the practice and application of both rights and an underlying avoidance of broader constitutional questions.